Figure of the father in relating to the upbringing: past, present and future - Ricardo López Marín; Alonso Molina Rodríguez; María Emilia Martínez Roche; Davinia Frutos Molina; Teresa Molina Rodríguez (Cultura de los Cuidados, 2012)
The current situation in the West reflects a gradual change of the father in the upbringing of their offspring, as reflected in its theory Madeleine Leininger, one must know the characteristics of this phenomenon to implement culturally congruent care. Based on the concept of Mercer “roles are not fixed, so no matter which person is responsible for performing the different roles” (Marriner, 2007) can mimic the maternal-paternal-filial subsidiary. We propose a qualitative research based on in-depth interview in order to study: parents (men) novice, and discussion groups professional midwives as the most representative figure and is directly involved with women’s reproductive health and care the newborn. Thus we can say that the typical family idea is accepted as is in crisis around the nineties, there emerges the figure of the new parents, a concept introduced by Bonino (2003). We met a father whose presence in the care of children is of great importance in the proper development of these (Alberdi Escario, 2007). Therefore we must work on the model to define the New Parent involvement in raising it. The midwife is the professional most qualified to serve as agents of change.